2019
DOI: 10.2147/ijn.s218248
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carbon Nanotube Reinforced Hydroxyapatite Nanocomposites As Bone Implants: Nanostructure, Mechanical Strength And Biocompatibility</p>

Abstract: PurposeHydroxyapatite (HA) is a biologically active ceramic which promotes bone growth, but it suffers from relatively weak mechanical properties. Multi-walled carbon nanotubes (MWCNTs) have high tensile strength and a degree of stiffness that can be used to strengthen HA; potentially improving the clinical utility of the bone implant.MethodsHA was precipitated by the wet precipitation method in the presence of pristine (p) or functionalised (f) MWCNTs, and polyvinyl alcohol (PVA) or hexadecyl trimethyl ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, nHap has poor mechanical strength restricting its use . Strategies to improve this problem without sacrificing its biocompatibility include incorporating reinforcement materials, such as zirconia, nanodiamond, alumina, carbon fibers, CNTs, and others. , CNTs have aroused intense interest due to their outstanding physiological properties to mimic the nanoscale dimensions of nHap and collagen fibers in natural bone. , The superficial modification of CNTs by exposure to oxygen plasma introduces polar groups that change their wettability and ability for incorporation into polymer composites. , This hydrophilic characteristic facilitates the adsorption of proteins essential in mediating cell adhesion, growth, and the formation of an extracellular matrix. , Therefore, the combination of CNTs with synthetic polymeric materials can be effective for promoting bone tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, nHap has poor mechanical strength restricting its use . Strategies to improve this problem without sacrificing its biocompatibility include incorporating reinforcement materials, such as zirconia, nanodiamond, alumina, carbon fibers, CNTs, and others. , CNTs have aroused intense interest due to their outstanding physiological properties to mimic the nanoscale dimensions of nHap and collagen fibers in natural bone. , The superficial modification of CNTs by exposure to oxygen plasma introduces polar groups that change their wettability and ability for incorporation into polymer composites. , This hydrophilic characteristic facilitates the adsorption of proteins essential in mediating cell adhesion, growth, and the formation of an extracellular matrix. , Therefore, the combination of CNTs with synthetic polymeric materials can be effective for promoting bone tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of favorable properties and biocompatibility of chitosan electrospun composite biomaterials for a variety of uses [ 19 ]. Carbon nanotubes can also be used to improve chitosan scaffolds, which may represent an attractive option due to their tensile strength, high flexibility, promising bioactivity and good electrical conductivity [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This research group were continued to improve composites for the highest mechanical performance and bioactivity materials for bone substitute [15,16]. Several studied have attempted to apply CNT as a new method to the expectation of improving the mechanical properties of polyethene [17] and hydroxyapatite [18]. For bone tissue engineering, many studies have concluded that the use of hydroxyapatite with polyethene [19,20] and CNT [21] provides excellent results in mechanical and biocompatibility properties.…”
Section: Introductionmentioning
confidence: 99%